2000
DOI: 10.1006/aphy.2000.6049
|View full text |Cite
|
Sign up to set email alerts
|

Charges from Dressed Matter: Physics and Renormalisation

Abstract: Gauge theories are characterised by long range interactions. Neglecting these interactions at large times, and identifying the Lagrangian matter fields with the asymptotic physical fields, leads to the infra-red problem. In this paper we study the perturbative applications of a construction of physical charges in QED, where the matter fields are combined with the associated electromagnetic clouds. This has been formally shown, in a companion paper, to include these asymptotic interactions. It is explicitly dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 23 publications
6
105
0
Order By: Relevance
“…This has been taken [1] to mean that one cannot describe charged particles in gauge theories. In a series of papers [2][3][4][5][6] we have shown that this conclusion is overly hasty: it is in fact possible to construct gauge invariant operators whose S-matrix elements are free of infra-red divergences. These fields have been shown to asymptotically recover a particle description of charges and to have a rich structure which is physically reflected in the cancellation of both soft and phase divergences.…”
Section: Introductionmentioning
confidence: 99%
“…This has been taken [1] to mean that one cannot describe charged particles in gauge theories. In a series of papers [2][3][4][5][6] we have shown that this conclusion is overly hasty: it is in fact possible to construct gauge invariant operators whose S-matrix elements are free of infra-red divergences. These fields have been shown to asymptotically recover a particle description of charges and to have a rich structure which is physically reflected in the cancellation of both soft and phase divergences.…”
Section: Introductionmentioning
confidence: 99%
“…(It is in fact clear from the start that the Lagrangian matter cannot hope to do this since it is not gauge invariant.) That such fields exist has been shown elsewhere [16] and that their Green's functions have a good pole structure has been amply demonstrated, see, e.g., [17][18][19]. These are the physical fields which should be identified with the charged particles seen in experiment.…”
Section: Discussionmentioning
confidence: 93%
“…The cubic term in the interaction Hamiltonian (19), which comes from the J µ 1 term in (20), is made up of two parts, J µ 11 and J µ 12 . These two terms are similar in their structure and both contribute to the problem of infra-red divergences.…”
Section: Scalar Qed: the Infra-red Approximationmentioning
confidence: 99%
“…It is thus natural to ask whether they can be used in practical work. The answer is yes, as we have shown in a detailed series of calculations [7,8]. For the purposes of showing the particle nature of our dressed fields the main point to note is that the on-shell Green's functions of these gauge invariant variables have a good pole structure.…”
Section: Perturbative Testsmentioning
confidence: 88%